DEVELOPING STUDENTS' SPEAKING ABILITY THROUGH STORYTELLING - Setiawaty, Yetty (2012)
This study attempted to investigate the effect of storytelling technique to develop students' speaking ability. It used a quasi-experimental design which involved two groups. The data obtained from the tests, questionnaires and interviews. The results showed that the storytelling technique developed students' speaking ability because there was a significant difference between the post-test scores of students in experimental and control groups. Overall, students' attitudes toward the implementation of storytelling technique were positive because they enjoyed the learning process and they were interested in the story. Finally, all these indicate that storytelling technique is worth implementing by teachers in their classrooms. Keywords: Speaking, Storytelling, Technique.